Assessment of gingival zenith position and distance from vertical bisecting midline in the maxillary anterior dentition − An observational study - Devapriya Appukuttan; Priyanka K Cholan; Canungo Ragothaman Ashwini; Sreenivasagan Swapna (Wolters Kluwer Medknow Publications, 2018)
Background: Esthetics in the maxillary anterior segment is determined by both the hard and soft tissues. Gingival contour plays a vital role in pink esthetics. The most common apical position of the marginal gingiva is referred to as gingival zenith (GZ). This study aimed to assess the position and distance of the GZ from the vertical bisecting midline (VBM) in the anterior maxillary dentition in a sample of South Indian population. Materials and Methods: A total of 105 participants were recruited based on specific inclusion and exclusion criteria. Following recruitment, alginate impressions were made, and dental cast were poured. A total of 630 anterior teeth were evaluated on the cast. The position of the GZ was marked, and a vertical line was drawn through the point. The VBM was drawn on the cast based on the crown width. Using magnification loupes (2.5×) and calibrated digital vernier caliper, the distance between the GZ and VBM was measured twice for each tooth, and the average reading was recorded. The position of GZ was recorded as mesial, distal, or coinciding with the VBM. Results: Majority of the right and left maxillary central incisors and lateral incisors were placed distal to the VBM measuring a mean distance of 0.7 ± 0.4 and 0.76 ± 0.36 mm, respectively, for centrals and 0.59 ± 0.3 and 0.62 ± 0.31 mm, respectively, for laterals. The GZ of both the right and left canines were mesial to the VBM at a mean distance of 0.59 ± 0.4 and 0.61 ± 0.3 mm, respectively. Conclusion: Familiarity with the position and distance of the GZ enables the dentist to plan an appropriate esthetic rehabilitation for the patients based on the population in question.